Pelatihan Budidaya Tanaman Hydroponic - Noersanti, Lina; Juniarti, Juniarti; Almurni, Siti; Akhmadi, Ali; Bramanta, Giraldi Sapta (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta (BPJP - STEI), 2024)
The objective of implementing this activity is to ensure that participants gain a comprehensive understanding of the hydroponic plant cultivation process and are able to engage in hands-on practices ranging from the seeding phase, transplanting seedlings to mature beds, to the care and resolution of potential challenges that may arise throughout the planting to harvest process. The methodology employed in the execution of this activity involves both training sessions and practical experiences conducted at the BKM Urban Hydroponic Garden in RW 12, Kayumanis, Tanah Sareal, Bogor, with guidance provided over the course of one month throughout the plant cultivation process. The outcomes of this Community Service Program (PKM) are deemed successful, as evidenced by the harvest results of hydroponic vegetables using the Nutrient Film Technique (NFT) method achieving a success rate of 92%, while the Wick System method attains a 100% success rate. The most suitable hydroponic vegetable cultivation model for implementation in urban household yards is identified as the Wick model.